Molecular and electronic structure of terminal and alkali metal-capped uranium(V) nitride complexes - King, David M.; Cleaves, Peter A.; Wooles, Ashley J.; Gardner, Benedict. M.; Chilton, Nicholas F.; Tuna, Floriana; Lewis, William; McInnes, Eric J.L.; Liddle, Stephen T. (Nature Publishing Group, 2016)
Determining the electronic structure of actinide complexes is intrinsically challenging because inter-electronic repulsion, crystal field, and spin–orbit coupling effects can be of similar magnitude. Moreover, such efforts have been hampered by the lack of structurally analogous families of complexes to study. Here we report an improved method to U≡N triple bonds, and assemble a family of uranium(V) nitrides. Along with an isoelectronic oxo, we quantify the electronic structure of this 5f1 family by magnetometry, optical and electron paramagnetic resonance (EPR) spectroscopies and modelling. Thus, we define the relative importance of the spin–orbit and crystal field interactions, and explain the experimentally observed different ground states. We find optical absorption linewidths give a potential tool to identify spin–orbit coupled states, and show measurement of UV···UV super-exchange coupling in dimers by EPR. We show that observed slow magnetic relaxation occurs via two-phonon processes, with no obvious correlation to the crystal field.